The studies of thixotropic properties of waxy crude oil from White Tiger and Rong fields - Bich, Ha Van (Vietnam Journal of Mechanics, 1996)
As in production and transport of waxy crude oil, and as in practical rheological studies of non-Newtonian liquids, it is very important to find and characterize its thixotropic properties. There are some ways to study this phenomenon, but still existing equations can not quantifiably describe the time dependent behavior of thixotropic liquids with acceptable accuracy, using in this case an exponential or hyperbolic functions.